Unravelling the neurochemical maze: neurotransmitters, neuropeptides and novel drug modes of action based on epilepsy pathophysiology - M. Dhall; R. Kadian; P. Sharma; A. Hooda; P. Kumar; P. Mudgal; K. Singh; A. Arya; N. Rani (Эпилепсия и пароксизмальные состояния)
The brain is extremely complicated three dimensional structures made up of interconnected neurons and neuroglia cells. It entails all type of functions of our body whether we are healthy or in disease conditions. Brain is accountable for our connectivity with the surroundings; all this is performed by an organized and systemic electrical activity of neurons by which they communicate messages to and from the brain. The abnormal electrical activity leading to the intense outburst of impulses, results in the development of epilepsy. Epilepsy is typified by recurrent, unprovoked seizures as a result excessive, hypersynchronous discharge of neurons occurs in the brain. Nearly 1% of the population throughout the worldwide is suffering from epilepsy and almost 75% begins at childhood. The patients almost one third are resistant to current available antiepileptic drugs. We don’t have the deep knowledge of the pathophysiology of the disease which can prove useful in further research for drugs with new mechanisms of action for diseases. This paper covers the role various neurotransmitters and neuropeptides in the pathophysiology of epilepsy. Our objective is to introduce the scientists with that aspect of the disease which may prove useful for further development of new drugs of epilepsy to overcome the resistance shown by the patientsorithm.